2022
DOI: 10.1186/s12903-022-02661-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased dental visits in patients with rheumatoid arthritis: a secondary cohort analysis of population based claims data

Abstract: Objective To study the utilization of dental care in patients with rheumatoid arthritis (RA) and compare the incidence of common dental disorders in patients with and without RA. Methods This data used in this study was from the population-based Taiwan's National Health Insurance Research Database. We identified 1337 patients with newly diagnosed RA between January 2000 and December 2012. We also identified 13,370 individual without a diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Our study offers epidemiological evidence for the association between RA and mouth ulcers from a genetic perspective. Similarly, a cohort analysis indicated a higher incidence of mouth ulcers in the RA population [adjusted HR (hazard ratio) = 1.24, p = 0.003] ( Juan et al, 2022 ). A real-world study revealed that mouth ulcers were associated with an increased risk of RA, suggesting that mouth ulcers may act as early indicators of systemic autoimmune conditions (HR = 1.19, p = 0.003) ( Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our study offers epidemiological evidence for the association between RA and mouth ulcers from a genetic perspective. Similarly, a cohort analysis indicated a higher incidence of mouth ulcers in the RA population [adjusted HR (hazard ratio) = 1.24, p = 0.003] ( Juan et al, 2022 ). A real-world study revealed that mouth ulcers were associated with an increased risk of RA, suggesting that mouth ulcers may act as early indicators of systemic autoimmune conditions (HR = 1.19, p = 0.003) ( Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Oral manifestations of RA have attracted increasing attention owing to their prevalent occurrence ( Silvestre-Rangil et al, 2016 ). Significantly, population-based research revealed a higher frequency of dental consultations in RA patients and an elevated prevalence of various dental pathologies ( Juan et al, 2022 ). A meta-analysis demonstrated an increased risk of RA in individuals with periodontal disease, which was notably more pronounced in instances of prolonged disease duration ( Qiao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%